Sex, menstrual cycle, and hormonal contraceptives influences on global–local processing. (December 2021) - Marful, A.; Paolieri, D.; Bernal, A.
Abstract: The effect of sex hormones on global–local tasks has rarely been studied, offering, when done, conflicting results possibly modulated by the congruency between hierarchical stimuli, and by the attentional demands. Here, we examined the global advantage (GA) effect in men (with high testosterone levels), women in the mid-luteal phase (with high levels of estradiol and progesterone), in the ovulatory phase (with high estradiol but low progesterone levels); and in the early follicular phase and with hormonal contraceptive (HC) use (with low sex hormone levels). The level of processing (global–local), the congruency (congruent vs. incongruent), and attentional demands (divided vs. selective) were manipulated. The divided-incongruent condition was sensible to estradiol and progesterone levels and, in this condition, mid-luteal women performed more locally while men performed more globally. The selective-incongruent condition was sensible to the testosterone level and, in this condition, men were faster. The HC group showed a congruency effect in the GA reaction times (RTs) during both, divided and selective conditions. Finally, the GA RTs of the ovulatory group differed from the early follicular and mid-luteal groups only in the congruent-selective condition, but the performance was not related with sex hormone levels. This result is interpreted in relation with the brain effects of estradiol in the absence but not in the presence of progesterone. Thus, sex, menstrual cycle, HC, task difficulty and sex hormones seem to modulate performance in the global–local task. These factors represent an important source of variability in studies focused on the processing of hierarchical stimuli and allow apparently inconsistent data to be explained. Highlights: Global advantage (GA) in a global–local task manipulating congruence and attention. Follicular, ovulatory, luteal, and hormonal contraceptive women and men show differences. Some GA effects correlate with testosterone, estradiol (E) and progesterone (P) levels. Other differences may depend on the effects of E in the absence but not presence of P. All these factors represent a source of variability in global–local effects.